Seasonality in Diffusive Methane Emissions Differs Between Bog Microforms - Jentzsch, Katharina; Männistö, Elisa; Marushchak, Maija E.; Rettelbach, Tabea; Golde, Lion; Korrensalo, Aino; Hashemi, Joshua; Delden, Lona; Tuittila, Eeva‐Stiina; Knoblauch, Christian; Treat, Claire C. (Global change biology, 2025)
ABSTRACT Wetlands are the largest natural source of atmospheric methane (CH4), but substantial uncertainties remain in the global CH4 budget, partly due to a mismatch in spatial scale between detailed in situ flux measurements and coarse‐resolution land surface models. In this study, we evaluated the importance of capturing small‐scale spatial heterogeneity within a patterned bog to better explain seasonal variation in ecosystem‐scale CH4 emissions. We conducted chamber‐based flux measurements and pore water sampling on vegetation removal plots across different microtopographic features (microforms) of Siikaneva bog, southern Finland, during seasonal field campaigns in 2022. Seasonal and spatial patterns in CH4 fluxes were analyzed in relation to key environmental and ecological drivers. High‐resolution (6 cm ground sampling distance) drone‐based land cover mapping enabled the extrapolation of microscale (< 0.1 m2) fluxes to the ecosystem scale (0.75 km2). Methane emissions from wetter microforms (mud bottoms and hollows) closely followed seasonal changes in peat temperature and green leaf area of aerenchymatous plants, while emissions from drier microforms (high lawns and hummocks) remained seasonally stable. This constancy was attributed to persistently low water tables, which moderated environmental fluctuations and reduced seasonality of CH4 production, CH4 oxidation and plant‐mediated transport. The strong spatial pattern in CH4 emissions and their seasonal dynamics made both the magnitude and seasonal cycle of ecosystem‐scale emissions highly sensitive to the areal distribution of microforms. Our findings underscore the need to integrate microscale spatial variability into CH4 modelling frameworks, as future shifts in peatland hydrology due to climate change may alter the balance between wet and dry microforms—and with it, the seasonal and annual CH4 budget. This study shows that small‐scale landscape features within a boreal bog strongly influence seasonal patterns of methane emissions. By combining ground‐based measurements with high‐resolution drone mapping, the research highlights that wetter areas dominate methane emissions in spring and summer, while emissions from drier areas gain importance in the fall. These contrasting seasonal dynamics highlight the need to incorporate fine‐scale spatial variation into climate models predicting methane release from wetlands.